The Pengenbangan - Toni Rahmanto; Insih Wilujeng (Postgraduate, University of Mataram, 2024)
Improving of physics learning process in vocational schools is very urgent to do so that it can improve the problem-solving skills. The purpose of this study was to produce student worksheets based on the engineering design process to practice physics problem-solving skills. This research method is research and development (R&D) using the ADDIE model. The research instruments consisted of learning observation sheets, interview sheets, feasibility & practicality assessment sheets, student response questionnaires, and questions. Product implementation as well as legibility assessment using 10th-grade automotive engineering students. Student worksheets are equipped with assignments to train students' problem-solving skills. To find out the criteria for increasing students' problem-solving abilities, the N-Gain equation is used. The results of the assessment showed that the student worksheets met the criteria of being very eligible (92.67%) and Very Practical (98.20%). Analysis of problem-solving tasks shows an average value of 88.89. As for the test results, it is known that as many as 78% of students are included in the High criteria, and 22% of students are included in the Moderate criteria. The conclusion of the research is that the use of EDP-based student worksheets can improve the problem-solving skills of students.